Structured diabetes education program for improving self-care behavior in primary care settings of Puducherry: Evidence from a randomized controlled trial - Mamta Gehlawat; Subitha Lakshminarayanan; Sitanshu Sekhar Kar (Wolters Kluwer Medknow Publications, 2019)
Context: Diabetes self-management education plays a critical role in improving patients' clinical outcome and quality of life. Aims: This study aims to study the effectiveness of a structured diabetes educational program on improvement of self-care behavior among type 2 diabetics in urban Primary Health Centres (PHCs) of Puducherry. Settings and Design: A community-based open-label parallel-arm randomized controlled trial was conducted in two randomly selected urban PHCs of Puducherry during December 2015-February 2017. Subjects and Methods: Using systematic random sampling, 157 eligible participants were recruited in intervention and control PHCs each. Sociodemographic, disease characteristics, and anthropometric measures were captured using a pretested questionnaire at baseline. Self-care behavior was recorded with Summary of Diabetes Self-Care Activities scale. Intervention consisted of structured diabetes education sessions with distribution of information leaflets and self-care kits to the intervention-arm participants, while control arm received standard care. At the end of 6 months, endline assessment was done for both groups. Data were analyzed by intention-to-treat, per-protocol, and difference-in-difference analysis using STATA. Results: Footcare increased significantly by 1.95 days/week compared to control arm, while a moderate change of 0.49 days/week in diet compliance and a minimal change of 0.10 days/week in physical activity were observed. Medication adherence, regular blood sugar testing, and smoking behavior also showed improvement in intervention arm. Conclusions: A structured education program that is culturally tailored showed an overall improvement in self-care behavior. This research supports the need for structured education program for diabetics to empower them and improve self-care practices. Trial registration: CTRI/2017/06/008772